On the Fly Design: Evolving a Collaborative System to Support Active Learning - Gonçalves, Fabrício Matheus; Reis, Julio Cesar dos; Prado, Alysson; Baranauskas, M. Cecília C. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2015)
Technologies in the current networked world have supported new ways of communication especially for the young; learning and teaching in online platforms could take advantage of them. In this article, we argue that if we are to design solutions that make sense and meet the different and complex communication needs of stakeholders in educational scenarios, we need to include them in the design cycle. We propose a method to involve the interested parties during the whole software lifecycle, which we are calling “on the fly design”. The method has been experimented in real scenarios of Computer Science disciplines. Results show the effectiveness of the proposal in the building and evolving of a collaborative system to support active learning.